2017
DOI: 10.37358/rc.17.1.5381
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Porosity of Fe62-xCo10WyMexY8B20-y Alloys in the Amorphous and Crystalline States (where: Me = Mo, Nb; x = 0, 1, 2; y = 0, 1, 2)

Abstract: The investigated crystalline and amorphous samples were obtained by crystallization of the liquid alloy on a water-cooled copper plate and by an injection-casting method, respectively. In each case, the structure of the samples was determined by examination of the obtained X-ray diffraction patterns. The diffraction patterns of samples produced by the injection casting method were characterized by a single broad peak called the amorphous halo. The samples produced by the crystallization method were shown to fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…At the same time, even small addition/substitution of d block elements can influence both HM and magnetic properties significantly [10]. The full understanding of the interactions taking place between substituted structure elements is therefore necessity both from a purely scientific point of view as well as from the applications point [11][12][13][14].…”
mentioning
confidence: 99%
“…At the same time, even small addition/substitution of d block elements can influence both HM and magnetic properties significantly [10]. The full understanding of the interactions taking place between substituted structure elements is therefore necessity both from a purely scientific point of view as well as from the applications point [11][12][13][14].…”
mentioning
confidence: 99%
“…Keywords: Amorphous materials, metals and alloys, Bulk metallic glasses, microstructure, X-ray diffraction Metallic amorphous materials despite their topological and chemical disorder very often show magnetic ordering [1][2][3][4][5][6][7]. Years of research have shown that many of these materials are characterized by excellent ferromagnetic properties, frequently finding their application in electrical industry mainly as magnetic cores for transformers, chokes and electric motors [8,9].…”
mentioning
confidence: 99%
“…Typically for the production of a material having good soft magnetic properties [4][5][6][7] especially low coercivity and low core losses, the rapid solidification of melted alloy technique is used [8]. This results in obtaining of material that is characterized by lack of long range order and which has good magnetic homogeneity.…”
mentioning
confidence: 99%